2015
DOI: 10.14283/jarcp.2015.58
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Hospitalized Old Medical Patients; How Active Are They, and What

Abstract: Objective: To examine how physically active Danish old medical patients are during hospitalization and to achieve knowledge of motivation and barriers to physical activity. Background: Functional decline in frail old patients during hospitalization is an important clinical problem with potential long-lasting undesirable outcomes and complications. Design: A mixed methods study including qualitative and quantitative methods. Methods: Patients >60 years of age were recruited at two medical departments during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the physical environment and lack of available resources do not encourage patients to become active. Our study identified a number of factors within the domain of Environmental Context and Resources that were not identified in previous studies [ 17 , 21 27 ], such as unnecessary waiting for HCPs (and ways to reduce this), the use of a bed or wheelchair to take patients to examinations, creating separate areas for sleeping and daytime activities, the availability of technology (e.g., interactive projections, virtual bike rides), attractive places (e.g., coffee corner, exercise room, garden) and activities (e.g., exhibitions, games, crafts, performances). To create a hospital culture aimed at improving older adults’ PA behaviour, our findings suggest that clinicians and researchers should consider reorganising care processes and organisational processes, restructuring the physical hospital environment and creating sufficient resources.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, the physical environment and lack of available resources do not encourage patients to become active. Our study identified a number of factors within the domain of Environmental Context and Resources that were not identified in previous studies [ 17 , 21 27 ], such as unnecessary waiting for HCPs (and ways to reduce this), the use of a bed or wheelchair to take patients to examinations, creating separate areas for sleeping and daytime activities, the availability of technology (e.g., interactive projections, virtual bike rides), attractive places (e.g., coffee corner, exercise room, garden) and activities (e.g., exhibitions, games, crafts, performances). To create a hospital culture aimed at improving older adults’ PA behaviour, our findings suggest that clinicians and researchers should consider reorganising care processes and organisational processes, restructuring the physical hospital environment and creating sufficient resources.…”
Section: Discussionmentioning
confidence: 79%
“…Several studies have investigated barriers and enablers to PA behaviour during hospital stay for acute care in older adults, from the perspectives of patients [ 17 , 21 ], healthcare professionals (HCPs) [ 22 – 24 ] or both [ 25 – 27 ]. Brown et al were the first to explore barriers to PA from the perspectives of patients and HCPs.…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent interventions require qualified personnel and multiple resources for their application, both of which are considered important barriers to the implementation of physical activity programmes in acutely hospitalised older adults 56. In contrast, ambulatory activities may be easier and simpler to implement in hospital settings,57 58 hence such interventions may be a cost-effective solution to reduce the negative consequences of excessive bed-time in hospitalised older adults 59. Nevertheless, the information provided in this study supports tailored physical activity advice adapted to individual preferences, needs and availability of resources,60 which may facilitate the adoption of a patient-centred care approach 61…”
Section: Discussionmentioning
confidence: 87%
“…At the end of hospitalization, despite the resolution of the condition for which they were admitted, frail patients are typically discharged in a worse functional status. It has been demonstrated that the muscle strength of elderly people gradually decreases at a rate of 1.5 to 3.5% per year, and if confined to bed for a long period, this loss occurs only one day after the discharge from the hospital [3,4]. Among patients that are bedridden, only one in four says that he/she is satisfied with his/her current life [5].…”
Section: Introductionmentioning
confidence: 99%